Indonesian Islam between Particularity and Universality - Meuleman, J.H. (Studia Islamika, 1997)
The issue of whether and to what extent Islam is part of the universal Islamic religion and civilization or a symptom of local specialties, has been answered in different ways by various scientists and politicians. The debate on this issue ever arise during the colonial era and continuing to the present.DOI: 10.15408/sdi.v4i3.773